2015
DOI: 10.1016/j.aquatox.2014.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the sensitivity, responsiveness and reproducibility of primary rainbow trout hepatocyte vitellogenin expression as a screening assay for estrogen mimics

Abstract: Vitellogenin (Vtg) induction in primary fish hepatocytes has been proposed as an in vitro screening assay for ER agonists and antagonists, but has not yet been used extensively as a high-throughput screening tool due to poor reproducibility, sensitivity and overall feasibility. The present work has evaluated the role of seasonal variation, normalization, optimal culture and assay conditions on the sensitivity, responsiveness and reproducibility of in vitro vtg gene mRNA and protein expression in rainbow trout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 69 publications
3
24
0
Order By: Relevance
“…These bioassays offer a high-throughput and multi-endpoint testing capacity. Primary hepatocytes from fish has been demonstrated to be a highly versatile multiendpoint screening assay by testing a suite of endpoints ranging from assessment of cytotoxicity to characterisation of their molecular MoA (Finne et al, 2007;Hultman et al, 2015aHultman et al, , 2015bPetersen and Tollefsen, 2011;Tollefsen et al, 2008a). These analyses include determination of potential estrogen receptor (ER) agonists and antagonists by measuring their binding to and activation/inhibition of ER and downstream processes such as the ER-mediated production of the egg-yolk precursor protein vitellogenin (Vtg) Tollefsen, 2011, 2012;Tollefsen et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…These bioassays offer a high-throughput and multi-endpoint testing capacity. Primary hepatocytes from fish has been demonstrated to be a highly versatile multiendpoint screening assay by testing a suite of endpoints ranging from assessment of cytotoxicity to characterisation of their molecular MoA (Finne et al, 2007;Hultman et al, 2015aHultman et al, , 2015bPetersen and Tollefsen, 2011;Tollefsen et al, 2008a). These analyses include determination of potential estrogen receptor (ER) agonists and antagonists by measuring their binding to and activation/inhibition of ER and downstream processes such as the ER-mediated production of the egg-yolk precursor protein vitellogenin (Vtg) Tollefsen, 2011, 2012;Tollefsen et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…Tollefsen et al (2003) observed a density-dependent increase in Vtg production up to 500 000 cells/ml, whereas higher densities led to reductions in Vtg production in primary hepatocytes from salmon. In this study, a lower cell density than previously used for Atlantic cod (Ellesat et al, 2011;Søfteland et al, 2010), rainbow trout (Hultman et al, 2015b), plaice, and long rough dab (Ellesat et al, 2011) were found to best balance the response and efficiency (number of plates per million cells) of the Arctic char hepatocyte assay. Cell densities in a similar range as that used in the current study have previously been used to study Vtg induction in primary hepatocytes from Oryzias latipes and Oreochromis mossambicus (Kim and Takemura, 2003;Kordes et al, 2002;Riley et al, 2004, see supplementary Table S4 for more information).…”
Section: Isolation and Exposure Of Arctic Char Hepatocytesmentioning
confidence: 73%
“…and coworkers published in the Feburary 2015 issue of Aquatic Toxicology (Hultman et al, 2015). The authors mentioned that Vitellogenin (Vtg) induction in primary fish hepatocytes has been proposed as an in vitro screening assay for ER agonists and antagonists, but has not yet been used extensively as a high-throughput screening tool due to poor reproducibility and sensitivity.…”
Section: Primary Hepatocytes Vitellogenin Mrna Reliability Validitymentioning
confidence: 99%
“…The authors mentioned that Vitellogenin (Vtg) induction in primary fish hepatocytes has been proposed as an in vitro screening assay for ER agonists and antagonists, but has not yet been used extensively as a high-throughput screening tool due to poor reproducibility and sensitivity. So they evaluated the role of seasonal variation, normalization, optimal culture and assay conditions on the sensitivity and reproducibility of in vitro vtg gene mRNA and protein expression in rainbow trout (Oncorhynchus mykiss) primary hepatocytes using the xenoestrogen 17␣-ethynylestradiol (EE2) as a test chemical (Hultman et al, 2015). They reported that primary hepatocytes display a relatively high individual and seasonal variation in both Vtg mRNA and protein induction potential, although less variance was observed in assay sensitivity (Hultman et al, 2015).…”
Section: Primary Hepatocytes Vitellogenin Mrna Reliability Validitymentioning
confidence: 99%
See 1 more Smart Citation